(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study addresses risk management and the enhancement of cybersecurity in Saudi companies, a critical issue in the face of rapid digital transformation. The research aims to analyze the risk management strategies employed by Saudi companies and how these strategies enhance cybersecurity to protect vital data and assets. A multi-faceted research methodology was utilized, incorporating descriptive analysis to evaluate the current risk management situation, quantitative methods through surveys and questionnaires, and qualitative interviews with cybersecurity experts. The study focused on identifying the major risks faced by Saudi companies, whether technological, financial, or organizational, and the tools and technologies used to mitigate these risks. The results highlighted the effectiveness of preventive measures such as the use of security monitoring systems, encryption, and continuous employee training. The study also explored the challenges companies face in implementing cybersecurity strategies, particularly given the evolving nature of cyber threats. The study concluded that Saudi companies need to adopt integrated risk management strategies, which include raising employee awareness, collaborating with governmental and private entities, and utilizing artificial intelligence technologies to address future threats. The study also recommended continuous improvement and updating of cybersecurity policies to ensure the protection of digital assets and maintain business continuity in the face of cyber crises.